Vietnamese Immigrants in Poland - Three Decades of Experience - Bodziany, Marek (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Three decades of common experience of the Poles and the Vietnamese in Poland invites reflection on chances of their cultural assimilation and over the coming years social inclusion as well. Indeed, their shared history on Polish soil goes back to the 1950s, however, a new stage in the mutual relationships was the result of the expansion of Vietnamese immigrants on Poland’s territory after 1989 followed by the collapse of the Eastern Bloc. Today, on the grounds of retrospective analyzes, a number of questions arise relating to the reasons for Vietnamese people’s immigration to Poland as well as concerning their existence in the foreign and culturally homogeneous environment. The scale of immigration, the cultural distinctiveness of the Vietnamese, the specificity of their social structure and existential problems fully justify the importance of undertaking research on this very interesting nationality. Moreover, they direct attention to the phenomenon encumbered with a social paradox. This phenomenon refers to the Vietnamese’s ability to adapt at both social and economic levels, whereas the paradox concerns the lack of links between the social sphere (underpinned by relatively positive relations with the Poles) and the economic one (relating to economic activity and entrepreneurship) and the inclination to cultural assimilation. Received 28th August 2017; Revised 20th October 2017; Accepted 30th October 2017